Value Chain Analysis of Orange Commodity in the Bantama Market, Kumasi, Ghana - Jiah Sayson; Sanu Jacob; Wawan Sujarwo; Soleman Imbiri; Dewi Saraswati; Winfred Nazziwa (Journal of Tropical Ethnobiology, 2020)
The performanceof thelocal sub-sector of orange in Bantama, Kumasi should be improved. This study aims to improve the performance of the local orange value chain in the Bantama market using rich picture analysis, scenario analysis, cigar box analysis, stakeholders’analysis, and SWOT analysis. The study suggests two strategic objectives, (1)the Bantama orange traders association (BOTA) coped with lack of storage facilities, which is expected that BOTA is linked directly to at least three major orange processors in Bantama by conducting stakeholders meeting between BOTA and orange processors, and a memorandum of understanding between BOTA and orangeprocessors; (2) the local government promoted the orange industry of Bantama, which is expected thatBOTA advocated to the local government for the establishment of market storage facility by preparingadvocating plan by BOTA, and consultation meetings with local government.